The Effectiveness of the Power of Two Strategy on the Student’s Reading Ability - Sulaiman; Muhammad Iqbal Ripo Putra (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
This pre experimental study was carried out at the English Education Department of IKIP-PGRI Pontianak. The population was the third semester students and the sample consisted of one class. The sampling technique used was cluster random sampling.. The technique of data collection in this research apply menstrument technique. The instruments used to collect the data was reading test. The tool of data collection apply in this research was pre-test and pos-test. The finding was the power of two strategy was effective to the student’s reading ability, it show that in the effec size the power of two strategy categorize strong effect to the student’s reading ability. Based on the result of the research, it is recommended that the teachers and the students should use the power of two strategy as one of alternative strategy in teaching reading